Effect of SAQ Training and Circuit Resistance Training on Selected Physiological and Bio Motor Components of Football Players - B.ANDREW, Dr.A.MAHABOOBJAN, A.ROBINSON, S.SATHYANARAYANAN, R.VIJAYAKUMAR (South Eastern European Journal of Public Health, 2025)
Introdution: SAQ programmes break speed down into three main areas of skills, speed, agility and quickness. Speed, agility, and quickness (SAQ) training is a type of physical training that focuses on developing the speed, agility, and quickness of an athlete. While SAQ training can be used to improve the performance of any athlete, it is most commonly used by athletes who participate in sports that require these skills, such as football, basketball, soccer, and hockey. A circuit resistance training programme usually has 10 to 15 stations per circuit. The circuit is repeated two to three times so that the total time of continuous exercise is 20 to 30 min. Circuit resistance training is usually performed 3 days/wk for at least 6 week. This method of training is ideal for subjects with a limited amount of time for exercise. Objectives: This study was designed to investigate the effect of saq training and circuit resistance training on selected physiological components of football players. Methods: To achieve the purpose of the study (N=45) forty five men football players were selected from affiliated colleges of Periyar University, Salem, Tamilnadu, India as subjects. The age of the subjects ranged from 19 to 23 years. The selected subjects were divided into three equal groups (N=15). Group I underwent saq training. Group II underwent circuit resistance training. Group III acted as control group who did not undergo any specialized training program other than their daily routine. The physiological components such as vital capacity, vo2 max and resting pulse rate; and the bio motor components such as leg explosive power, agility and muscular endurance were selected as dependent variables. The physiological components were assessed by digital dry spiro meter, 12 minutes cooper test and digital heart rate monitor test; and the bio motor components were assessed by vertical jump, illinois agility test and sit ups test respectively. The subjects were concerned with their particular training for a period of twelve weeks, alternatively three days per week. The collected data from three groups prior to and immediately after the training programme on selected criterion variables were statistically analyzed with analysis of covariance (ANCOVA). Conclusions: The level of confidence was fixed at 0.05 for all the cases to test the hypothesis. The result of the study reveals that the saq training and circuit resistance training groups achieved significant improvement on selected physiological and bio motor components such as vital capacity, vo2 max and resting pulse rate; and the bio motor components such as leg explosive power, agility and muscular endurance of college men football players.